Liquid crystal polyester composition and molded article

By adding high molecular weight polyethylene, fibrous filler and fatty acid metal salts to the liquid crystal polyester composition, the problem of low mold release of thin-walled and complex molded bodies is solved, and a more efficient molding process and better molding is achieved finished product quality.

CN119452032APending Publication Date: 2025-02-14SUMITOMO CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380050077.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-13
Filing Date
2023-06-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When manufacturing thin-walled and complex electrical and mechanical parts, the easiness of the molded body to be removed from the mold (mold release ability), resulting in increased working hours and deformation or damage of the molded body.

Method used

A liquid crystal polyester composition containing liquid crystal polyester and high molecular weight polyethylene is used, and fibrous fillers such as glass fibers and metal salts of fatty acids are added thereon to improve the mold release property of the molded body.

Benefits of technology

By improving the mold release property of the molded body, the working time requirement is reduced and the risk of deformation and damage of the molded body is reduced, and the overall performance of the molded body is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211287370000161
    Figure BDA0005211287370000161
  • Figure BDA0005211287370000171
    Figure BDA0005211287370000171
  • Figure BDA0005211287370000191
    Figure BDA0005211287370000191
Patent Text Reader

Abstract

The present invention uses a liquid crystal polyester composition containing a liquid crystal polyester and a specific high molecular weight polyethylene. The liquid crystal polyester composition is characterized in that the limiting viscosity of the high-molecular-weight polyethylene is 10-18 dL / g, the volume median diameter (d50) of the high-molecular-weight polyethylene is 65 [mu] m or less, and the content of the high-molecular-weight polyethylene is 0.1-1.2 parts by mass per 100 parts by mass of the liquid crystal polyester.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal polyester composition and a molded body.

[0002] This application claims priority based on Japanese Patent Application No. 2022-112311 filed in Japan on July 13, 2022, and the contents are incorporated herein by reference. Background Art

[0003] Liquid crystal polyesters are used as molding materials for manufacturing various products and parts represented by electrical and electronic parts due to their high heat resistance, high strength and excellent melt fluidity. In particular, liquid crystal polyesters are preferably used as molding materials for manufacturing molded bodies having thin-walled parts or molded bodies having complex shapes, taking advantage of their excellent melt fluidity.

[0004] For example, Patent Document 1 discloses a liquid crystal polyester resin mixture obtained by mixing a liquid crystal polyester, a filler, and a high molecular weight polyethylene.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-12898 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, electric and electronic parts and mechanical parts have been increasingly thinner and more complex in shape as equipment has become more advanced in recent years, with higher performance and higher output, or smaller and lighter.

[0010] In the molding of thin-walled and complex molded bodies, the demolding property, which indicates the ease of removing the molded body from the mold, is sometimes poor. In this case, the work time in removing the molded body may increase or the molded body may be deformed or damaged. Patent Document 1 does not examine the demolding property.

[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a liquid crystal polyester composition having further improved releasability, which indicates the ease with which a molded article can be removed from a mold, and a molded article containing the same.

[0012] Means for solving problems

[0013] In order to solve the above-mentioned problems, the present invention includes the following means.

[0014] [1] A liquid crystal polyester composition comprising a liquid crystal polyester and a high molecular weight polyethylene, wherein the limiting viscosity of the high molecular weight polyethylene is greater than or equal to 10 dL / g and less than or equal to 18 dL / g, the volume median diameter (d50) of the high molecular weight polyethylene is less than or equal to 65 μm, and the content of the high molecular weight polyethylene is greater than or equal to 0.1 parts by mass and less than or equal to 1.2 parts by mass relative to 100 parts by mass of the liquid crystal polyester.

[0015] [2] The liquid crystal polyester composition according to [1], further comprising a fibrous filler.

[0016] [3] The liquid crystal polyester composition according to [2], wherein the fibrous filler is glass fiber.

[0017] [4] The liquid crystal polyester composition according to [2] or [3], wherein the content of the fibrous filler is 20 parts by mass or more and 250 parts by mass or less relative to 100 parts by mass of the liquid crystal polyester.

[0018] [5] The liquid crystal polyester composition according to any one of [1] to [4], further comprising a metal salt of a fatty acid.

[0019] [6] The liquid crystal polyester composition according to [5], wherein the metal salt of the fatty acid is a metal salt of a fatty acid having 12 or more carbon atoms.

[0020] [7] The liquid crystal polyester composition according to any one of [1] to [6], wherein the liquid crystal polyester has a repeating unit represented by the following formula (1).

[0021] (1)-O-Ar 1 -CO-

[0022] In the above formula (1), Ar 1 Ar represents phenylene, naphthylene or biphenylene. 1 The hydrogen atoms in the above-mentioned groups may be substituted by halogen atoms, alkyl groups or aryl groups.

[0023] [8] The liquid crystal polyester composition according to [7], wherein the liquid crystal polyester has a repeating unit represented by the following formula (1), a repeating unit represented by the following formula (2), and a repeating unit represented by the following formula (3).

[0024] (1)-O-Ar 1 -CO-

[0025] (2)-CO-Ar 2 -CO-

[0026] (3)-X-Ar 3 -Y-

[0027] In the above formula (1), formula (2) and formula (3), Ar 1 Ar represents phenylene, naphthylene or biphenylene. 2 and Ar 3 Each independently represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4). X and Y each independently represent an oxygen atom or an imino group (-NH-). 1 ,Ar 2 or Ar 3 The hydrogen atoms in the above-mentioned groups may be independently substituted by a halogen atom, an alkyl group or an aryl group.

[0028] (4)-Ar 4 -Z-Ar 5 -

[0029] In the above formula (4), Ar 4 and Ar 5 Each independently represents a phenylene group or a naphthylene group. Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group or an alkylene group.

[0030] [9] A liquid crystal polyester composition according to any one of [1] to [8], wherein the limiting viscosity of the high molecular weight polyethylene is 11 dL / g or more and 16 dL / g or less, preferably 12 dL / g or more and 15 dL / g or less, the volume median diameter (d50) of the high molecular weight polyethylene is 5 μm or more and less than 65 μm, preferably 5 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, and the content of the high molecular weight polyethylene is 0.2 parts by mass or more and 1.0 parts by mass or less, preferably 0.3 parts by mass or more and 0.9 parts by mass or less, more preferably 0.4 parts by mass or more and 0.8 parts by mass or less, relative to 100 parts by mass of the liquid crystal polyester.

[0031]

[10] The liquid crystal polyester composition according to any one of [4] to [9], wherein the content of the fibrous filler is preferably 40 parts by mass or more and 200 parts by mass or less, and more preferably 50 parts by mass or more and 150 parts by mass or less, relative to 100 parts by mass of the liquid crystal polyester.

[0032]

[11] A liquid crystal polyester composition according to any one of [6] to

[10] , wherein the content of the metal salt of the fatty acid having 12 or more carbon atoms is 0.02 parts by mass or more and 0.15 parts by mass or less, preferably 0.02 parts by mass or more and 0.12 parts by mass or less, and more preferably 0.02 parts by mass or more and 0.09 parts by mass or less, relative to 100 parts by mass of the liquid crystal polyester.

[0033]

[12] A molded article comprising the liquid crystal polyester composition according to any one of [1] to

[11] .

[0034] Effects of the Invention

[0035] According to the present invention, it is possible to provide a liquid crystal polyester composition having further improved releasability, which indicates the ease with which a molded article can be removed from a mold, and a molded article containing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a perspective view showing an example of a molded product including the liquid crystal polyester composition according to the present embodiment.

[0037] Figure 2A It is a cross-sectional view showing the mold used in this example.

[0038] Figure 2B This is a photograph showing the first plate in the mold used in this example. DETAILED DESCRIPTION

[0039] (Liquid Crystal Polyester Composition)

[0040] The liquid crystal polyester composition of the present embodiment contains a liquid crystal polyester and a high molecular weight polyethylene. The limiting viscosity of the high molecular weight polyethylene is greater than 10 dL / g and less than 18 dL / g. The volume median diameter (d50) of the high molecular weight polyethylene is less than 65 μm. The content of the high molecular weight polyethylene is greater than 0.1 parts by mass and less than 1.2 parts by mass relative to 100 parts by mass of the liquid crystal polyester.

[0041] <Liquid Crystal Polyester>

[0042] The liquid crystal polyester used in the present embodiment is a polyester that exhibits liquid crystallinity in a molten state, and is preferably a polyester that melts at a temperature of 400° C. or lower.

[0043] The flow start temperature of the liquid crystal polyester is preferably 260°C or higher, more preferably 260°C or higher and 400°C or lower, and further preferably 260°C or higher and 380°C or lower.

[0044] In this specification, the flow start temperature of the liquid crystal polyester is also called the fluid temperature or the flow temperature, which is the standard temperature for the molecular weight of the liquid crystal polyester (see Naoyuki Koide, "Liquid Crystal Polymer - Synthesis, Molding, and Applications -", ​​CMC Co., Ltd., June 5, 1987, p. 95).

[0045] The flow start temperature refers to the temperature at which the liquid crystal polyester is subjected to a flow tester at 9.8 MPa (100 kg / cm 2) under a load of 4°C / min while being heated to melt, and the viscosity of the liquid crystal polyester is 4800 Pa·s (48000 poise) when extruded from a nozzle having an inner diameter of 1 mm and a length of 10 mm.

[0046] The liquid crystal polyester is preferably a wholly aromatic liquid crystal polyester using only aromatic compounds as raw material monomers.

[0047] The liquid crystal polyester preferably has a repeating unit represented by the following formula (1) (hereinafter referred to as "repeating unit (1)"). The liquid crystal polyester more preferably has the above repeating unit (1), a repeating unit represented by the following formula (2) (hereinafter referred to as "repeating unit (2)"), and a repeating unit represented by the following formula (3) (hereinafter referred to as "repeating unit (3)").

[0048] The liquid crystal polyester may have two or more types of repeating units (1) to (3), respectively and independently.

[0049] (1)-O-Ar 1 -CO-

[0050] (2)-CO-Ar 2 -CO-

[0051] (3)-X-Ar 3 -Y-

[0052] In the above formula (1), formula (2) and formula (3), Ar 1 Ar represents phenylene, naphthylene or biphenylene. 2 and Ar 3 Each independently represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (4). X and Y each independently represent an oxygen atom or an imino group (-NH-). 1 ,Ar 2 or Ar 3 The hydrogen atoms in the above-mentioned groups may be independently substituted by a halogen atom, an alkyl group or an aryl group.

[0053] (4)-Ar 4 -Z-Ar 5 -

[0054] In the above formula (4), Ar 4 and Ar 5 Each independently represents a phenylene group or a naphthylene group. Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group or an alkylene group.

[0055] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0056] Examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-hexyl, 2-ethylhexyl, n-octyl and n-decyl. The alkyl group preferably has 1 to 10 carbon atoms.

[0057] Examples of the aryl group include phenyl, o-tolyl, m-tolyl, p-tolyl, 1-naphthyl and 2-naphthyl. The aryl group preferably has 6 to 20 carbon atoms.

[0058] In the case where the above hydrogen atoms are replaced by these groups, the number of 1 ,Ar 2 or Ar 3 The number of the above groups represented is preferably 2 or less, and more preferably 1 or less, respectively, independently.

[0059] Examples of the alkylene group include a methylene group, an ethylene group, an isopropylene group, an n-butylene group, and a 2-ethylhexylene group. The number of carbon atoms in the alkylene group is preferably 1 to 10.

[0060] The repeating unit (1) is a repeating unit derived from a predetermined aromatic hydroxycarboxylic acid. 1 is a repeating unit of 1,4-phenylene (a repeating unit derived from p-hydroxybenzoic acid), Ar 1 is a repeating unit of 2,6-naphthylene (a repeating unit derived from 6-hydroxy-2-naphthoic acid), more preferably Ar 1 The repeating unit is 1,4-phenylene.

[0061] The term "origin" as used herein means that the chemical structure of the functional group that contributes to the polymerization of the raw material monomer changes, and no other structural changes occur.

[0062] The repeating unit (2) is a repeating unit derived from a predetermined aromatic dicarboxylic acid. The repeating unit (2) is preferably Ar 2 is a repeating unit of 1,4-phenylene (a repeating unit derived from terephthalic acid), Ar 2 is a repeating unit of 1,3-phenylene (a repeating unit derived from isophthalic acid), Ar 2 is a repeating unit of 2,6-naphthylene (a repeating unit derived from 2,6-naphthalenedicarboxylic acid), Ar 2 is a repeating unit of diphenyl ether-4,4'-diyl (a repeating unit derived from diphenyl ether-4,4'-dicarboxylic acid), and more preferably Ar 2 is a repeating unit of 1,4-phenylene and / or Ar 2 The liquid crystal polyester preferably contains Ar 2 The repeating unit is 1,4-phenylene and Ar2 The repeating unit (2) is a 1,3-phenylene repeating unit.

[0063] The repeating unit (3) is a repeating unit derived from a predetermined aromatic diol, aromatic hydroxyamine or aromatic diamine. 3 is a repeating unit of 1,4-phenylene (a repeating unit derived from hydroquinone, p-aminophenol or p-phenylenediamine), Ar 3 is a repeating unit of 4,4'-biphenylene (a repeating unit derived from 4,4'-dihydroxybiphenyl, 4-amino-4'-hydroxybiphenyl or 4,4'-diaminobiphenyl), and more preferably Ar 3 It is a repeating unit of 4,4'-biphenylene.

[0064] The content of the repeating unit (1) is preferably 30 mol% or more, more preferably 30 mol% or more and 80 mol% or less, further preferably 40 mol% or more and 70 mol% or less, particularly preferably 45 mol% or more and 65 mol% or less, based on the total amount of all repeating units.

[0065] As the content of the repeating unit (1) increases, melt fluidity, heat resistance, strength and rigidity tend to be improved. However, if it is too much, the melting temperature and melt viscosity tend to be high, and the temperature required for molding tends to be high.

[0066] In the present specification, the total amount of all repeating units refers to a value obtained by dividing the mass of each repeating unit constituting the liquid crystal polyester by the formula weight of each repeating unit to obtain the equivalent amount (molar) of each repeating unit and adding them together.

[0067] The content of the repeating unit (2) is preferably 35 mol% or less, more preferably 10 mol% to 35 mol%, further preferably 15 mol% to 30 mol%, particularly preferably 17.5 mol% to 27.5 mol%, based on the total amount of all repeating units.

[0068] The content of the repeating unit (3) is preferably 35 mol% or less, more preferably 10 mol% or more and 35 mol% or less, further preferably 15 mol% or more and 30 mol% or less, particularly preferably 17.5 mol% or more and 27.5 mol% or less, based on the total amount of all repeating units.

[0069] The ratio of the content of repeating unit (2) to the content of repeating unit (3) is expressed as [content of repeating unit (2)] / [content of repeating unit (3)] (mol / mol), and is preferably 0.9 / 1 to 1 / 0.9, more preferably 0.95 / 1 to 1 / 0.95, and further preferably 0.98 / 1 to 1 / 0.98.

[0070] The liquid crystal polyester may have repeating units other than the repeating units (1) to (3), but the content thereof is preferably 10 mol% or less, more preferably 5 mol% or less, based on the total amount of all repeating units.

[0071] The liquid crystal polyester preferably has a repeating unit in which X and Y are each an oxygen atom as the repeating unit (3) because the melt viscosity tends to be low. The liquid crystal polyester more preferably has only a repeating unit in which X and Y are each an oxygen atom as the repeating unit (3).

[0072] The liquid crystal polyester can be produced by melt-polymerizing raw material monomers corresponding to the repeating units constituting the liquid crystal polyester and solid-phase polymerizing the obtained polymer (hereinafter sometimes referred to as a "prepolymer") The melt polymerization may be performed in the presence of a catalyst.

[0073] In the present embodiment, the liquid crystal polyester may be used alone or in combination of two or more.

[0074] The content of the liquid crystal polyester in the liquid crystal polyester composition of the present embodiment is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, based on 100% by mass of the total amount of the liquid crystal polyester composition.

[0075] The content of the liquid crystal polyester in the liquid crystal polyester composition of the present embodiment is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less, based on 100% by mass of the total amount of the liquid crystal polyester composition.

[0076] For example, the content of the liquid crystal polyester in the liquid crystal polyester composition of the present embodiment is preferably 30% by mass or more and 80% by mass or less, more preferably 35% by mass or more and 70% by mass or less, and further preferably 40% by mass or more and 60% by mass or less, relative to 100% by mass of the total amount of the liquid crystal polyester composition.

[0077] <High molecular weight polyethylene>

[0078] The high molecular weight polyethylene used in the present embodiment has an intrinsic viscosity of 10 dL / g to 18 dL / g, preferably 11 dL / g to 16 dL / g, and more preferably 12 dL / g to 15 dL / g.

[0079] As such a high molecular weight polyethylene, a commercially available product can be used, and examples thereof include polyethylene of various grades under the trade name MIPELON (registered trademark) manufactured by Mitsui Chemicals, Inc.

[0080] The limiting viscosity of high molecular weight polyethylene can be measured as follows.

[0081] High molecular weight polyethylene was diluted with decalin to obtain multiple dilution solutions with different high molecular weight polyethylene concentrations. The flow time of each dilution solution was measured with a capillary viscometer at a measurement temperature of 135°C to obtain the reduced viscosity. The relationship between the high molecular weight polyethylene concentration and the reduced viscosity was plotted and the intercept when the linear approximation was extrapolated was taken as the limiting viscosity (dL / g).

[0082] The molecular weight of the high molecular weight polyethylene used in the present embodiment is preferably 1,000,000 or more and 3,500,000 or less, and more preferably 1,250,000 or more and 3,000,000 or less.

[0083] The molecular weight of the high molecular weight polyethylene can be determined by calculating the viscosity average molecular weight from the above-mentioned limiting viscosity based on the following formula (*).

[0084] Viscosity average molecular weight Mv = 5.37 × 10 4 ×[η] 1.37 (*)

[0085] [η]: limiting viscosity (dL / g), solvent: decalin, measurement temperature: 135°C

[0086] The volume median diameter (d50) of the high molecular weight polyethylene refers to a particle diameter at which the cumulative value in the volume-based particle size distribution determined by the Coulter counter method reaches 50%.

[0087] The volume median diameter (d50) of the high molecular weight polyethylene used in the present embodiment is 65 μm or less, preferably 5 μm or more and less than 65 μm, more preferably 5 μm or more and 50 μm or less, and further preferably 5 μm or more and 40 μm or less.

[0088] The volume median diameter (d50) of the high molecular weight polyethylene may be 5 μm or more and 63 μm or less.

[0089] In the liquid crystal polyester composition of the present embodiment, the content of the high molecular weight polyethylene is greater than 0.1 parts by mass and less than 1.2 parts by mass, preferably greater than 0.1 parts by mass and less than 1.2 parts by mass, more preferably greater than 0.2 parts by mass and less than 1.0 parts by mass, further preferably greater than 0.3 parts by mass and less than 0.9 parts by mass, and particularly preferably greater than 0.4 parts by mass and less than 0.8 parts by mass, relative to 100 parts by mass of the liquid crystal polyester.

[0090] The total content of the high molecular weight polyethylene and the liquid crystal polyester may be 20 parts by mass or more and 100 parts by mass or less, or 30 parts by mass or more and 90 parts by mass or less, based on 100 parts by mass of the liquid crystal polyester composition.

[0091] <Other ingredients>

[0092] The liquid crystal polyester composition of the present embodiment may contain, in addition to the liquid crystal polyester and the high molecular weight polyethylene, one or more fibrous fillers, metal salts of fatty acids, resins other than the liquid crystal polyester, and additives other than these as necessary.

[0093] Fibrous filler

[0094] The liquid crystal polyester composition of the present embodiment preferably further contains a fibrous filler. By further containing a fibrous filler, the strength of the molded product represented by tensile strength, flexural strength, and impact strength becomes higher.

[0095] The fibrous filler may be a fibrous inorganic filler or a fibrous organic filler.

[0096] From the viewpoint of imparting strength to a molded body and easiness of obtaining, the fibrous filler is preferably glass fiber. As the glass fiber, E glass is preferred.

[0097] When a fibrous filler is used in the present embodiment, the fibrous filler may be used alone or in combination of two or more.

[0098] In the liquid crystal polyester composition of the present embodiment, the content of the fibrous filler is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, and further preferably 50 parts by mass or more, relative to 100 parts by mass of the liquid crystal polyester. In addition, the content of the fibrous filler is preferably 250 parts by mass or less, more preferably 200 parts by mass or less, and further preferably 150 parts by mass or less, relative to 100 parts by mass of the liquid crystal polyester.

[0099] The content of the fibrous filler may be 165 parts by mass or less, or 175 parts by mass or less, based on 100 parts by mass of the liquid crystal polyester.

[0100] The content of the fibrous filler in the liquid crystal polyester composition of the present embodiment is preferably 20 parts by mass or more and 250 parts by mass or less, more preferably 40 parts by mass or more and 200 parts by mass or less, and further preferably 50 parts by mass or more and 150 parts by mass or less, based on 100 parts by mass of the liquid crystal polyester.

[0101] Metal salts of fatty acids

[0102] The liquid crystal polyester composition of this embodiment preferably further contains a metal salt of a fatty acid. By further containing a metal salt of a fatty acid, the metering time during molding is stable and the uneven metering time can be suppressed. In addition, the average metering time during molding can be shortened. As a result, the breakage of the fibrous filler contained in the resin pellets can be reduced during molding, and the strength of the molded body is improved.

[0103] An example of the metal salt of a fatty acid in the present embodiment is a metal salt of a fatty acid having 12 or more carbon atoms.

[0104] The carbon number of the fatty acid is preferably 12 or more and 28 or less, and more preferably 12 or more and 18 or less.

[0105] Specific examples of the metal salt of a fatty acid include lithium laurate, calcium laurate, barium laurate, lithium stearate, barium stearate, sodium stearate, potassium stearate, calcium stearate, aluminum stearate, magnesium behenate, calcium behenate, and barium behenate.

[0106] The metal salts of fatty acids may be used alone or in combination of two or more.

[0107] In the liquid crystal polyester composition of this embodiment, the content of the metal salt of the fatty acid is preferably 0.02 mass parts to 0.15 mass parts, more preferably 0.02 mass parts to 0.12 mass parts, and further preferably 0.02 mass parts to 0.09 mass parts, relative to 100 mass parts of the liquid crystal polyester.

[0108] 《Resins other than liquid crystal polyesters》

[0109] Examples of resins other than liquid crystal polyesters include thermoplastic resins other than liquid crystal polyester resins such as polypropylene, polyamide, polyesters other than liquid crystal polyester resins, polysulfone, polyphenylene sulfide, polyether ketone, polycarbonate, polyphenylene ether, and polyetherimide; and thermosetting resins such as phenolic resins, epoxy resins, polyimide resins, and cyanate resins.

[0110] Other additives include fillers other than the above-mentioned fibrous fillers, metering stabilizers other than the above-mentioned metal salts of fatty acids, release agents other than the above-mentioned high molecular weight polyethylene, antioxidants, heat stabilizers, ultraviolet absorbers, antistatic agents, surfactants, flame retardants, colorants, etc.

[0111] The shape of the liquid crystal polyester composition of the present embodiment is not particularly limited, and examples thereof include a powdery form and a pelletized form.

[0112] Among the liquid crystal polyester compositions of this embodiment, from the perspective of stability of metering time during molding and improvement of mechanical strength of the molded body, preferably, there is mentioned a composition containing the liquid crystal polyester, the high molecular weight polyethylene, the fibrous filler and the metal salt of the fatty acid.

[0113] The above-mentioned preferred composition is particularly preferably used as a pellet mixture, for example, from the viewpoint of controllability of fiber length unevenness and formation of long fibers in the molded portion.

[0114] In the liquid crystal polyester composition of the present embodiment, it is particularly effective for mold release properties during molding that the volume median diameter (d50) of the high molecular weight polyethylene contained therein is 65 μm or less.

[0115] In the liquid crystal polyester composition of the present embodiment, by controlling the particle size of the high molecular weight polyethylene, the content of the high molecular weight polyethylene and / or the limiting viscosity of the high molecular weight polyethylene, in addition to improving the demolding property, the average metering time during molding can be shortened, and the strength of the molded body represented by tensile strength, bending strength, and impact strength can be improved. In addition, with respect to the impact strength, the standard deviation indicating the unevenness of the strength is also reduced.

[0116] (Molding body)

[0117] The molded product of the present embodiment includes the liquid crystal polyester composition of one embodiment of the present invention described above.

[0118] One embodiment of the molded article can be produced by a known molding method such as injection molding using the liquid crystal polyester composition of the above-mentioned embodiment.

[0119] The molded article of this embodiment can be used for all applications to which liquid crystal polyesters are generally applicable, and is particularly suitable for applications in the automotive field.

[0120] Examples of applications in the automotive field include injection-molded articles for automotive interior materials and injection-molded articles for automotive exterior materials.

[0121] The molded article of the present embodiment is used, for example, as a shock absorbing member in a crash box mounted in a vehicle.

[0122] Hereinafter, the embodiments will be described with reference to the drawings. In all the drawings, the dimensions, ratios, etc. of the components are different from the actual dimensions from the viewpoint of the ease of viewing of the drawings.

[0123] The molded body 500 has an injection molded part 530 using a liquid crystal polyester composition as a molding material. The injection molded part 530 includes a main body 510 and a flange 520 integrally molded therewith.

[0124] The main body 510 has a honeycomb structure in which a plurality of cylindrical cells 512 protruding from the flange 520 are arranged without gaps. The honeycomb structure may be a structure in which cylindrical cells in the shape of hexagonal columns are arranged without gaps. The cylindrical cells 512 are formed into a cylindrical shape in which the end surface on the flange 520 side is closed and the end surface on the opposite side of the flange 520 is open. The height of the cylindrical cells 512 is, for example, 20 to 200 mm. The thickness of the cell wall 514 is, for example, 0.5 to 5 mm.

[0125] Since the molded body 500 is made of resin, it is lightweight, and since it has a honeycomb structure, the impact energy absorption performance is improved.

[0126] Since the molded body 500 has a complex shape and a wide contact area with the elongated center pin, it is difficult to remove the molded body from the mold. Specifically, the following disadvantages may occur: the molded body cannot be removed from the mold; a large number of operations are required to protrude the demolding pin; the flange portion 520 is damaged during removal; and the impact marks of the demolding pin remain on the flange portion 520.

[0127] The liquid crystal polyester composition of the present embodiment has high releasability indicating the ease with which the molded article can be removed from the mold even when a molded article having a complicated shape such as the molded article 500 is injection molded.

[0128] The present invention has the following aspects.

[0129]

[13] A cushioning member comprising an injection-molded part produced using the liquid crystal polyester composition described in any one of [1] to

[11] above,

[0130] The injection molded part includes a main body having a honeycomb structure filled with a plurality of cylindrical cells.

[0131]

[14] The buffer component according to

[13] , wherein the mass ratio of the liquid crystal polyester and the fibrous filler contained in the above-mentioned injection molded part is: 25 to 60 parts by mass of the fibrous filler relative to 40 to 75 parts by mass of the liquid crystal polyester, preferably 25 to 55 parts by mass of the fibrous filler relative to 45 to 75 parts by mass of the liquid crystal polyester, more preferably 30 to 55 parts by mass of the fibrous filler relative to 45 to 70 parts by mass of the liquid crystal polyester, and further preferably 30 to 50 parts by mass of the fibrous filler relative to 50 to 70 parts by mass of the liquid crystal polyester.

[0132] Example

[0133] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to these examples.

[0134] [Measurement of Flow Start Temperature of Liquid Crystal Polyester and Pellets]

[0135] Using a flow tester ("CFT-500EX" manufactured by Shimadzu Corporation), about 2 g of the sample was filled into a barrel equipped with a die head having a nozzle with an inner diameter of 1 mm and a length of 10 mm. The sample was melted while being heated at a rate of 4°C / min under a load of 9.8 MPa, extruded from the nozzle, and the temperature at which a viscosity of 4800 Pa·s was measured as the flow start temperature.

[0136] [Determination of limiting viscosity of high molecular weight polyethylene]

[0137] The high molecular weight polyethylene was diluted with decalin to prepare a plurality of dilution solutions with different high molecular weight polyethylene concentrations. The flow time of each dilution solution was measured at a measurement temperature of 135°C using a capillary viscometer to determine the reduced viscosity. Then, the relationship between the high molecular weight polyethylene concentration and the reduced viscosity was plotted and the intercept when the linear approximation was extrapolated was determined as the limiting viscosity (dL / g).

[0138] [Determination of volume median diameter (d50) of high molecular weight polyethylene]

[0139] The volume median diameter (d50) of the high molecular weight polyethylene is measured as follows.

[0140] A sample was prepared by adding ISOTONII and Tween 20 to high molecular weight polyethylene and mixing. The volume median diameter (d50) of the sample was determined by the Coulter counting method. ISOTONII is an electrolyte for measurement manufactured by Beckman Coulter. Tween 20 is a surfactant.

[0141] The equipment and test conditions used:

[0142] As the Coulter counter, Multisizer 4 (manufactured by Beckman Coulter) was used.

[0143] Pore ​​size 100μm (measurement range from 2μm to 60μm)

[0144] Pore ​​size 280μm (measurement range from 5.6μm to 168μm)

[0145] Pore ​​size 400μm (measurement range from 9.7μm to 240μm)

[0146] <Preparation of resin material>

[0147] As the liquid crystal polyester, a powdery liquid crystal polyester (LCP1) and a powdery liquid crystal polyester (LCP2) were produced.

[0148] Furthermore, pure pellets (1) consisting only of liquid crystal polyester were produced.

[0149] Furthermore, resin pellets (1) in which glass fibers were impregnated with liquid crystal polyester were produced.

[0150] 《Manufacturing of powdered liquid crystal polyester (LCP1)》

[0151] In a reactor equipped with a stirrer, a torque meter, a nitrogen inlet pipe, a thermometer and a reflux cooler, p-hydroxybenzoic acid (994.5 g, 7.2 mol), 4,4'-dihydroxybiphenyl (446.9 g, 2.4 mol), terephthalic acid (299.0 g, 1.8 mol), isophthalic acid (99.7 g, 0.6 mol) and acetic anhydride (1347.6 g, 13.2 mol) and 0.9 g of 1-methylimidazole were added, and the interior of the reactor was fully substituted with nitrogen.

[0152] Thereafter, under a nitrogen gas stream, the temperature in the reactor was raised from room temperature to 150° C. over 30 minutes, and the mixture was maintained at 150° C. and refluxed for 1 hour.

[0153] Next, 1-methylimidazole (0.9 g) was added to the reactor, and the temperature was raised from 150° C. to 320° C. over 2 hours and 50 minutes while by-produced acetic acid and unreacted acetic anhydride were distilled off. The reaction was terminated when an increase in torque was confirmed, the contents were taken out, and cooled to room temperature to obtain a solid.

[0154] The obtained solid was pulverized with a pulverizer until the particle size became about 0.1 to 1 mm, and then the temperature was raised from room temperature to 250°C over 1 hour, from 250°C to 285°C over 5 hours, and maintained at 285°C for 3 hours under a nitrogen atmosphere to carry out solid phase polymerization.

[0155] After solid phase polymerization, cooling is performed to obtain a liquid crystal polyester (LCP1) in a powdery state.

[0156] The liquid crystal polyester obtained here has Ar 1 The repeating unit (1) is 60 mol% of 1,4-phenylene, Ar 2 The repeating unit (2) is 15 mol% of 1,4-phenylene, Ar 2 The repeating unit (2) is 5 mol% of 1,3-phenylene and Ar 3 The repeating unit (3) of 4,4'-biphenylene was 20 mol % and the flow starting temperature was 327°C.

[0157] 《Manufacturing of Powdered Liquid Crystal Polyester (LCP2)》

[0158] In a reactor equipped with a stirrer, a torque meter, a nitrogen inlet pipe, a thermometer and a reflux cooler, p-hydroxybenzoic acid (994.5 g, 7.2 mol), 4,4'-dihydroxybiphenyl (446.9 g, 2.4 mol), terephthalic acid (239.2 g, 1.44 mol), isophthalic acid (159.5 g, 0.96 mol) and acetic anhydride (1347.6 g, 13.2 mol) were charged, 1-methylimidazole (0.9 g) was added, and the inside of the reactor was fully substituted with nitrogen.

[0159] Thereafter, under a nitrogen gas stream, the temperature in the reactor was raised from room temperature to 150° C. over 30 minutes, and the mixture was maintained at 150° C. and refluxed for 1 hour.

[0160] Next, 1-methylimidazole (0.9 g) was added to the reactor, and the temperature was raised from 150° C. to 320° C. over 2 hours and 50 minutes while by-produced acetic acid and unreacted acetic anhydride were distilled off. The reaction was terminated when an increase in torque was confirmed, the contents were taken out, and cooled to room temperature to obtain a solid.

[0161] The obtained solid was pulverized with a pulverizer until the particle size became about 0.1 to 1 mm, and then the temperature was raised from room temperature to 220°C in 1 hour, from 220°C to 240°C in 0.5 hour, and maintained at 240°C for 10 hours under a nitrogen atmosphere to carry out solid phase polymerization.

[0162] After solid phase polymerization, cooling is performed to obtain a powdery liquid crystal polyester (LCP2).

[0163] The liquid crystal polyester obtained here has Ar 1 The repeating unit (1) is 60 mol% of 1,4-phenylene, Ar 2 The repeating unit (2) is 12 mol% of 1,4-phenylene, Ar 2 The repeating unit (2) is 8 mol% of 1,3-phenylene and Ar 3 The repeating unit (3) of 4,4'-biphenylene was 20 mol % and the flow starting temperature was 291°C.

[0164] 《Manufacturing of pure granules (1)》

[0165] The obtained powdery liquid crystal polyester (LCP2) was granulated by a twin-screw extruder (PMT47, manufactured by IKG) at a cylinder temperature of 290°C to produce pure pellets (1). The flow start temperature of the obtained pure pellets (1) was 284°C.

[0166] 《Manufacturing of resin pellets (1)》

[0167] The resin pellets (1) were produced as follows.

[0168] The extruder used was a GTS-40 extruder (manufactured by PLABOR Research Laboratory of Plastics Technology Co., Ltd.). The belt pulling machine used was an EBD-1500A (manufactured by AIMEX Corporation). The following glass fibers were used as the fibrous filler.

[0169] [Fiberglass]

[0170] GF1: Glass fiber roving (E glass, fiber diameter 10 μm, fineness 1400 g / 1000 m, manufactured by Nippon Electric Glass Co., Ltd.)

[0171] As the powdered liquid crystal polyester, the above-mentioned LCP1 and LCP2 were used.

[0172] A resin structure was obtained in which GF1 was 165 parts by mass relative to a total of 100 parts by mass of LCP1 and LCP2 (75 parts by mass of LCP1 and 25 parts by mass of LCP2). Specifically, molten LCP1 and LCP2 were supplied from the extruder and impregnated into GF1 to obtain a resin structure.

[0173] The obtained resin structure was pulled into a strand by the above-mentioned belt puller, sent to a pelletizer, and cut into a predetermined length (12 mm) along the longitudinal direction to obtain cylindrical resin pellets (1).

[0174] <Manufacturing of Liquid Crystal Polyester Composition>

[0175] (Comparative Example 1)

[0176] The resin pellets (1), pure pellets (1) and the metal salt of fatty acid (1) were mixed in the mixing ratio shown in Table 1 and under the molding conditions (A) described below to produce a liquid crystal polyester composition of Comparative Example 1.

[0177] The metal salt of fatty acid (1) was added in an amount of 0.06 parts by mass based on 100 parts by mass of the total of LCP1 and LCP2.

[0178] (Examples 1 to 5, Comparative Examples 2 to 3)

[0179] Resin pellets (1), pure pellets (1), high molecular weight polyethylene (1) to (5) and metal salts of fatty acids (1) were mixed in the proportions shown in Table 1 and under the molding conditions (A) described below to produce liquid crystal polyester compositions of Examples 1 to 5 and Comparative Examples 2 to 3.

[0180] The high molecular weight polyethylene (1) to (5) was added in an amount of 0.1 parts by mass to 100 parts by mass of LCP1 and LCP2 in total in Example 1; 1.2 parts by mass was added in Example 3; 0.6 parts by mass was added in each of Examples 2, 4 and 5; and 0.6 parts by mass was added in each of Comparative Examples 2 to 3.

[0181] The metal salt of fatty acid (1) was added in an amount of 0.06 parts by mass based on 100 parts by mass of the total of LCP1 and LCP2.

[0182] The high molecular weight polyethylene and the metal salt of fatty acid used are shown below.

[0183] High molecular weight polyethylene (1): limiting viscosity 14 dL / g, volume median diameter (d50) 32 μm, MIPELON (registered trademark) XM-221U manufactured by Mitsui Chemicals

[0184] High molecular weight polyethylene (2): limiting viscosity 13 dL / g, volume median diameter (d50) 11 μm, MIPELON (registered trademark) PM-200 manufactured by Mitsui Chemicals

[0185] High molecular weight polyethylene (3): limiting viscosity 14 dL / g, volume median diameter (d50) 64 μm, MIPELON (registered trademark) XM-330 manufactured by Mitsui Chemicals

[0186] High molecular weight polyethylene (4): limiting viscosity 5 dL / g, volume median diameter (d50) 132 μm, HI-ZEX MILLION (registered trademark) 030S manufactured by Mitsui Chemicals

[0187] High molecular weight polyethylene (5): limiting viscosity 30 dL / g, volume median diameter (d50) 171 μm, HI-ZEX MILLION (registered trademark) 630M manufactured by Mitsui Chemicals

[0188] Metal salt of fatty acid (1): calcium behenate, CS-7 manufactured by Nitto Kasei Kogyo Co., Ltd.

[0189] Table 1

[0190]

[0191] <Manufacturing of Molded Article>

[0192] The liquid crystal polyester composition of each example was molded into the above-mentioned Figure 1 A cushioning member was manufactured by using an injection molded part having a main body having a honeycomb structure in the same form as the molded body 500 shown in FIG.

[0193] [Molding conditions (A)]

[0194] Molding temperature: 300℃ for plasticizing part, 360℃ for plunger part

[0195] Screw speed 100rpm, back pressure 1MPa, injection speed 200mm / s, mold temperature 70℃, holding pressure 30MPa, holding time 5sec

[0196] The honeycomb structure possessed by the main body is a structure consisting of 32 cylindrical chambers in which the opening surface of the cylindrical chamber with a height of 80 mm is set to a roughly regular hexagonal shape and the curvature radius of each vertex is set to 2 mm in a top view, and the inner diameter of the chamber of the opening surface of the cylindrical chamber is formed to 13 mm, the inner diameter of the chamber of the end face on the flange side of the cylindrical chamber is formed to 12 mm, the chamber wall thickness of the opening surface of the cylindrical chamber is formed to 1 mm, the chamber wall thickness of the end face on the flange side of the cylindrical chamber is formed to 2 mm, and the thickness of the flange is formed to 5 mm.

[0197] [Evaluation of mold release properties]

[0198] The releasability indicating the ease of removing the molded body from the mold was evaluated in the following procedure.

[0199] exist Figure 2A In the figure, the mold 200 includes a first plate 210 , a second plate 220 , and a total of twelve demolding pins 232 .

[0200] The first plate 210 has a plurality of center pins 212 arranged in a horizontal direction. Figure 2B The photo shown in FIG. 2 shows one form thereof. The demolding pin 232 is located on the outer periphery of the center pin 212 and is arranged parallel to the center pin 212 .

[0201] Step (1) When the molded body (cushion member) is taken out from the mold 200, first, the first plate 210 and the second plate 220 are opened with a gap of 15 mm or more therebetween.

[0202] In step (2), the molded body is extruded from the first plate 210 by causing the demolding pin 232 to protrude to the right (toward the second plate 220 , in the direction of the arrow) under the following ejection conditions.

[0203] Ejection conditions for one operation: ejection force 5.4kN, ejection speed 5mm / sec

[0204] Step (3) The number of operations (stripper protrusion times) to protrude the stripper pin 232 until the distance (protrusion distance) of the molded body protruding from the first plate 210 reaches 15 mm is calculated. Then, the demolding property is evaluated based on the following evaluation criteria using the number of stripper protrusions as an index. The results are shown in Table 2.

[0205] Evaluation criteria for mold release

[0206] E (Excellent): The demolding device protrudes once.

[0207] G (Good): The demolding tool protrudes twice.

[0208] B (Bad): The ejector protruded 3 times or the molded product could not be removed from the mold.

[0209] Table 2

[0210]

[0211] <Manufacturing of Molded Body (2 mm Thick Dumbbell)>

[0212] Each test piece was produced by subjecting the liquid crystal polyester composition of each example to an injection molding process under the molding conditions (B) shown below.

[0213] Specifically, the liquid crystal polyester composition of each example was charged into the hopper of an injection molding machine TR450EH3 (manufactured by Sodick Corporation) and molded into a test piece having a thickness of 2 mm instead of the multipurpose test piece (type A1) (thickness 4 mm) according to JIS K7139 under the following molding conditions (B).

[0214] The gate was set as a film gate having a thickness of 2 mm from the upper side of the one-side clamping portion of the multipurpose test piece.

[0215] [Molding conditions (B)]

[0216] Molding temperature: 300℃ for plasticizing part, 360℃ for plunger part

[0217] Screw speed 100rpm, back pressure 1MPa, injection speed 20mm / s, mold temperature 100℃, holding pressure 70MPa, holding time 5sec

[0218] [Determination of average measuring time]

[0219] In the production of the molded body (2 mm thick dumbbell), 15 multi-purpose test pieces with a thickness of 2 mm were continuously molded, and the metering time during each molding from the 6th to the 15th piece was measured. Then, the average metering time of these 10 injections was calculated. The results are shown in Table 3.

[0220] [Determination of tensile strength]

[0221] For the multi-purpose test piece with a thickness of 2 mm manufactured in the above-mentioned <Manufacture of molded body (2 mm thick dumbbell)>, the test speed was set to 1 mm / min. In addition, the tensile strength (MPa) was measured in an atmosphere of 23°C and a relative humidity of 50% in accordance with JIS K7161 (Plastics - Test method for tensile properties) and ISO527.

[0222] An Instron universal testing machine (manufactured by Instron, 68TM-50) was used for the measurement. The measurement was performed on 5 samples, and the average value thereof was calculated. The results are shown in Table 3.

[0223] [Measurement of flexural strength]

[0224] A test piece of 10 mm in width × 80 mm in length × 2 mm in thickness was cut out from the center of the multipurpose test piece of 2 mm thickness produced in the above <Production of molded article (2 mm thick dumbbell)>. For the cut test piece, the test speed was set to 1 mm / min and the distance between the fulcrums was set to 32 mm. In addition, the flexural strength (MPa) in an atmosphere of 23°C and a relative humidity of 50% was measured in accordance with JIS K7171 (Plastics - Method for determining flexural properties) and ISO178.

[0225] An Instron universal testing machine (manufactured by Instron, 68TM-50) was used for the measurement. The measurement was performed on 5 samples, and the average value thereof was calculated. The results are shown in Table 3.

[0226] [Determination of impact strength and its standard deviation]

[0227] Charpy impact strength of unnotched test piece

[0228] From the center of the 2 mm thick multipurpose test piece produced in the above <Production of Molded Article (2 mm Thick Dumbbell)>, a test piece of 10 mm width×80 mm length×2 mm thickness was cut out to prepare a test piece without a notch.

[0229] The unnotched test piece was subjected to a Charpy impact test five times using a hammer of 4.0 J in accordance with ISO 179-1 and JIS K7111-1 (Plastics - Method for determining Charpy impact properties) to measure the impact strength (kJ / m 2 ) and its standard deviation. A pendulum impact tester (CEAST9050 manufactured by Instron) was used for this measurement.

[0230] The Charpy impact strength of the unnotched test piece was measured five times and the average value was used.

[0231] Charpy impact strength of notched test piece

[0232] The unnotched test piece was notched at a notch angle of 45° and a depth of 2 mm according to the method of ISO 2818 and JIS K7144 to produce a notched test piece. A notching tool (manufactured by Toyo Seiki Co., Ltd., Model A-4) was used for the notching.

[0233] The notched test piece was subjected to a Charpy impact test 5 times using a hammer of 4.0 J in accordance with ISO 179-1 and JIS K7111-1 to measure the impact strength (kJ / m 2 ) and its standard deviation. A pendulum impact tester (CEAST9050 manufactured by Instron) was used for this measurement.

[0234] The Charpy impact strength of the notched test piece was measured five times and the average value was used.

[0235] Table 3

[0236]

[0237] Explanation of symbols

[0238] 200 mold, 210 first plate, 212 center pin, 220 second plate, 232 demolding pin, 500 molded body, 510 main body, 512 cylindrical cavity, 514 cavity wall, 520 flange, 530 injection molding part

Claims

1. A liquid crystal polyester composition, which is a liquid crystal polyester composition containing a liquid crystal polyester and a high molecular weight polyethylene, wherein: The high molecular weight polyethylene has an intrinsic viscosity of 10 dL / g or more and 18 dL / g or less, The volume median diameter d50 of the high molecular weight polyethylene is less than 65 μm, The content of the high molecular weight polyethylene is 0.1 parts by mass or more and 1.2 parts by mass or less relative to 100 parts by mass of the liquid crystal polyester.

2. The liquid crystal polyester composition according to claim 1, wherein It further contains a fibrous filler.

3. The liquid crystal polyester composition according to claim 2, wherein The fibrous filler is glass fiber.

4. The liquid crystal polyester composition according to claim 2, wherein The content of the fibrous filler is 20 parts by mass or more and 250 parts by mass or less relative to 100 parts by mass of the liquid crystal polyester.

5. The liquid crystal polyester composition according to claim 1, wherein It further contains a metal salt of a fatty acid.

6. The liquid crystal polyester composition according to claim 1, wherein The liquid crystal polyester has a repeating unit represented by the following formula (1): (1)-O-Ar 1 -WHAT- In the formula (1), Ar 1 represents phenylene, naphthylene or biphenylene, Ar 1 The hydrogen atoms in the groups represented may be substituted by halogen atoms, alkyl groups or aryl groups. 7 . A molded article comprising the liquid crystal polyester composition according to claim 1 . The molded body according to claim 7 , which has a honeycomb structure.

Citation Information

Patent Citations

  • Liquid crystalline polyester resin mixture

    JP2003012898A

  • Signal processing device, wearable terminal, signal processing system, and signal processing method

    JP2022112311A